2022
DOI: 10.3390/ijerph19042274
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Health Effects on Deceit in Heterosexual Sexual-Affective Relationships: The Impact of the Preventive Socialization Program (PSP)

Abstract: Background: Health research has provided robust evidence of the negative effects caused by facing deceit in sexual-affective relationships. In this regard, several analyses have been conducted addressing psychological, family therapies, and educational interventions to improve marital problems. On the other hand, many investigations have addressed how the preventive socialization program (PSP), framed on the analysis of a dominant coercive discourse that is connected with the promotion of specific traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Coercive discourse in peer interactions fosters attraction to violence (Puigvert et al, 2019; Ruiz-Eugenio et al, 2020; Torras-Gómez et al, 2019), promoting relationships with dominant masculine models (Duque et al, 2022; Flecha et al, 2013; Puigvert et al, 2019; Rodrigues-Mello et al, 2021; Ruiz-Eugenio et al, 2020). These violent relationships can have consequences on health and work, among other elements, as identified in previous studies (Duque et al, 2020; Hawks et al, 2019; López de Aguileta, 2021; Miller, 2017; Puigvert-Mallar et al, 2022). Coercive discourse also generates a lack of consent in the affective–sexual relationships of young women (Beres et al, 2014; Burkett & Hamilton, 2012; Flecha et al, 2020, Hawks et al, 2019; Shumlich & Fisher, 2018).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Coercive discourse in peer interactions fosters attraction to violence (Puigvert et al, 2019; Ruiz-Eugenio et al, 2020; Torras-Gómez et al, 2019), promoting relationships with dominant masculine models (Duque et al, 2022; Flecha et al, 2013; Puigvert et al, 2019; Rodrigues-Mello et al, 2021; Ruiz-Eugenio et al, 2020). These violent relationships can have consequences on health and work, among other elements, as identified in previous studies (Duque et al, 2020; Hawks et al, 2019; López de Aguileta, 2021; Miller, 2017; Puigvert-Mallar et al, 2022). Coercive discourse also generates a lack of consent in the affective–sexual relationships of young women (Beres et al, 2014; Burkett & Hamilton, 2012; Flecha et al, 2020, Hawks et al, 2019; Shumlich & Fisher, 2018).…”
Section: Introductionmentioning
confidence: 68%
“…In this sense, education on consent requires incorporating new elements that support women throughout their affective–sexual socialization, mainly in awakening affective–sexual relationships. For example, existing research sheds light on overcoming coercive discourse through peer interactions and community involvement (Elboj-Saso et al, 2020; Puigvert-Mallart et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in this analytical grid, two main dimensions were included following the premises of the communicative methodology: exclusionary and transformative. The first ones refer to these barriers that make improvements difficult, the second ones are those realities that contribute to overcoming these difficulties (Puigvert-Mallart, et al 2022). The last step of this analytical procedure was the implementation of the content analysis which was deductively conducted considering the same categories and dimensions explained above and which are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, much research has shown the positive impact on the health of men who follow a model of new alternative masculinity, based essentially on friendships that help to promote healthier behaviors. This makes it possible to overcome the major problem regarding the health of men who follow the hegemonic masculinity model that has been noted in research for decades (Puigvert et. al, 2022;Ríos-González et.…”
Section: Mcs -Masculinities and Socialmentioning
confidence: 99%